Prenatal and Postnatal Supplementation with Lipid-Based Nutrient Supplements Reduces Anemia and Iron Deficiency in 18-Month-Old Bangladeshi Children: A Cluster-Randomized Effectiveness Trial. Issue 7 (13th June 2018) - Matias, Susana L; Mridha, Malay K; Young, Rebecca T; Khan, Md Showkat A; Siddiqui, Zakia; Ullah, Md Barkat; Vosti, Stephen A; Dewey, Kathryn G
Abstract: Background: Anemia, iron deficiency (ID), and iron deficiency anemia (IDA) among young children are public health concerns in developing countries. Objective: We evaluated the effects of small-quantity lipid-based nutrient supplements (LNSs) and micronutrient powder (MNP) on anemia, ID, and IDA in 18-mo-old Bangladeshi children. Methods: We enrolled 4011 pregnant women in a cluster-randomized effectiveness trial with 4 arms— 1 ) LNS-LNS: LNSs (including 20 mg Fe) for women daily during pregnancy and 6 mo postpartum and LNSs (including 9 mg Fe) for children daily from 6 to 24 mo of age (LNS-C); 2 ) IFA-LNS: iron (60 mg) and folic acid (IFA) for women daily during pregnancy and every other day for 3 mo postpartum and LNS-C for children; 3 ) IFA-MNP: IFA for women, and MNP (including 10 mg Fe) for children daily from 6 to 24 mo; and 4 ) IFA-Control: IFA for women and no child supplement. Hemoglobin, serum ferritin, and soluble transferrin receptor (sTfR) were assessed in a subsample of children ( n  = 1121) at 18 mo to identify anemia (hemoglobin <110g/L), ID (ferritin <12 µg/L or sTfR >8.3 mg/L), and IDA. Data were analyzed with the use of mixed-effects modeling. Results: Compared with the IFA-Control arm, hemoglobin was higher in the LNS-LNS and IFA-LNS arms and ferritin was higher and sTfR was lower in the LNS-LNS, IFA-LNS, and IFA-MNP arms; LNS-LNS children had reduced odds of anemia (OR: 0.46; 95% CI: 0.25, 0.84), high sTfR (OR: 0.47; 95% CI: 0.29, 0.73), and ID (OR: 0.45; 95% CI: 0.28, 0.71); and all 3 groups had lower odds of low ferritin [corrected for inflammation; OR (95% CI)—LNS-LNS: 0.29 (0.13, 0.63); IFA-LNS: 0.25 (0.11, 0.59); and IFA-MNP: 0.37 (0.18, 0.76)] and IDA [LNS-LNS: 0.35 (0.18, 0.67); IFA-LNS: 0.45 (0.24, 0.85); and IFA-MNP: 0.47 (0.26, 0.87)]. Conclusions: Home fortification using LNSs or MNP reduced IDA in 18-mo-old Bangladeshi children. The provision of LNSs in both pregnancy and childhood also reduced child anemia and ID. These findings are relevant to programs targeting similar populations. This trial was registered at www.clinicaltrials.gov as NCT01715038.